The Guttenberg bible : a memoir - Guttenberg, Steve, 1958- (Thomas Dunne Books, 2012)
This is the memoir of the highs and lows of Hollywood by the actor who starred in multiple iconic blockbusters such as Diner, Police Academy and Three Men and a Baby. "Forget being an actor. In this memoir, he tells a Horatio Alger story of how he became the star of some of the 80s' most successful blockbusters. He spent his early days sneaking onto the Paramount lot and meeting more celebrities and casting agents than most aspiring actors ever would. Even before Police Academy he had already worked with such luminaries as Sir Laurence Olivier and Gregory Peck. Later he shared the screen with actors like Mickey Rourke and Sharon Stone long before they became household names. He has lived through the addictive pull of worldwide celebrity (You're no one until you have a stalker, he learns), but he knew that his family would keep him grounded. His self-awareness and sense of humor about the ups and downs of fame make this one of the most candid Hollywood stories to date.